The impact of offensive duration on NBA success: a comparative analysis of Jordan's Chicago Bulls and Curry's Golden State Warriors - Amatria Jiménez, M.; Cook Vaquero, N. A.; Suarez-Llorca, C.; Pérez-Turpin, J. A. (Journal of Human Kinetics, 2025)
This study investigated the influence of offensive play duration on the competitive performance of two NBA teams with the most regular-season victories in the league history. Using observational methodology, differences in the length and speed of offensive actions and their corresponding shooting efficiency were examined. Results revealed significant contrasts in the play tempo, with one team favoring fast, explosive plays (Golden State Warriors) and the other adopting slower, more strategic maneuvers (Chicago Bulls). Despite these differences, both teams maintained comparable shooting success rates. This suggests that the ability to adjust the play tempo according to game circumstances and opponent characteristics is critical for maximizing offensive efficiency. Moreover, the study demonstrates that variability in possession duration is strongly linked to fatigue management and the balance between anaerobic and aerobic energy systems. This finding underscores the importance of tactical flexibility, as adjusting the pace and intensity of play can be a decisive factor in modern basketball success, where shorter, quicker, and more explosive plays are increasingly prevalent. The study concludes that dynamic time-of-possession management and adaptive efforts are key to optimizing high-level competitive performance.